Faktor-Faktor Penentu Prevalensi Stunting di Nusa Tenggara Barat: Analisis Spasial dengan Modifikasi Ketetanggaan - Nastiti, Kartika Tri; Luthfi, Zalfa Jihan; Ummah, Karimatul; Brilliant, Indira Ihnu; Setiawan, Ezra Putranda (Department of Mathematics, Universitas Negeri Gorontalo, 2025)
Stunting is one of the problems faced by the Indonesian population. In 2022, its prevalence in West Nusa Tenggara reached 18.5% and became the fourth highest in Indonesia. This study was conducted to identify the factors that can be used to explain the prevalence of stunting in West Nusa Tenggara using the spatial regression method. Considering that this province consists of two separate islands, Queen's contiguity matrix was modified to consider the connections between the islands. Based on the AIC values, the Spatial Durbin Model (SDM) becomes the best model for stunting prevalence. The research results show that the variables Human Development Index (HDI), ADHK Gross Regional Domestic Product, and the number of community health centers have a significant effect on the prevalence of stunting in West Nusa Tenggara. Of these three variables, the HDI variable has the greatest influence on reducing the prevalence of stunting in West Nusa Tenggara. The significance of the Spatial Durbin model shows that there is a spatial effect on the dependent and independent variables.